Pengaruh ROA, ROE Terhadap Harga Saham PT Bank Central Asia Tbk - Giantoro Pamungkas; Riski Wisnu Prakoso; Muhamad Rifki Aa Alifia; Fini Ikfini Maulaya; Anggi Anggraeni; Shaka Ramadhia (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
The purpose of this study is to see how Return on Assets (ROA) and Return on Equity (ROE) impact the stock price of PT Bank Central Asia Tbk (BBCA) during the period 2019–2023. ROE and ROA, which are considered to have a significant correlation with stock price movements in the capital market, are important metrics for assessing a company's financial performance. Quantitative methods are used in this study. Secondary data used consist of monthly stock prices listed on the Indonesia Stock Exchange and BBCA's annual financial statements. To see how ROA and ROE impact stock prices simultaneously and partially, using multiple linear regression analysis. The results of the study show that ROA has a positive and significant effect on BBCA's stock price, indicating that the company's efficiency in generating profits from its assets has a direct impact on stock price appreciation. On the other hand, ROE also has a positive and significant effect, indicating that the level of return on shareholder investment is one of the important factors in stock price assessments by investors.